Semantic retrieval and ranking of Semantic Web documents using free-form queries. (9th December 2008) - Spiliopoulos, Vassilis; Kotis, Konstantinos; Vouros, George A.
Recent advances in the Semantic Web research community actuated the experimentation with a variety of approaches concerning the retrieval of Semantic Web Documents (SWDs). Most approaches require that queries are formed in a structured and formal way. Given the inability of the majority of web users to express formal queries, this paper proposes an approach to SWDs' retrieval, aiming to support users to place queries, requiring no knowledge and skills for expressing these queries in a formal language. The paper discusses specific issues that are considered towards the retrieval of SWDs using free-form queries and presents an evaluated two-step approach.